Estimating the burden of minor ailment consultations in general practices and emergency departments through retrospective review of routine data in North East Scotland. (5th March 2015) - Fielding, Shona; Porteous, Terry; Ferguson, James; Maskrey, Vivienne; Blyth, Annie; Paudyal, Vibhu; Barton, Garry; Holland, Richard; Bond, Christine M; Watson, Margaret C
Abstract: Background: Minor ailment attendances in general practices and emergency departments (EDs) place significant burden on health care resources. Objectives: To estimate the prevalence and type of minor ailment consultations for adults in general practice and ED that could be managed in a community pharmacy. Methods: Retrospective review of routine data from general practices ( n = 2) and one ED in North East Scotland. Two independent consensus panels assessed each consultation summary to determine whether it represented a minor ailment. Outcomes included prevalence of consultations for minor ailments in general practice and ED and frequency of different minor ailment type that could be managed in community pharmacies. Results: In total, of the 494 general practice and 550 ED consultations assessed, 13.2% [95% confidence interval (CI): 18.6–25.9%] and 5.3% (95% CI: 4.0–8.0%), respectively, were categorized as minor ailments suitable for management in community pharmacies. Consensus among panel members was moderate for general practice consultations, but fair to poor for ED consultations. Agreement between uni- and multi-disciplinary panels was good. Applied to national data, these estimates would equate to 18 million general practice and 6500000 ED consultations that could be redirected to community pharmacy, equating to £1.1 billion in resources. Conclusion: Minor ailment consultations still present a major burden on higher cost settings. Effective strategies are needed to raise awareness among patients and health professionals regarding conditions that can be managed effectively in pharmacies and to change patient health-seeking behaviour for such conditions.